Local Government Discretion and Accountability : Application of a Local Governance Framework - World Bank (Washington, DC, 2013)
This report evaluates the framework of decentralization reforms instituted in decentralizing countries. Decentralization is a multi-faceted process which includes giving discretion to local governments and establishing accountability mechanisms at three different levels of governance: political, administrative and fiscal. Therefore, the analysis of the decentralization reforms should also be based on an inter-disciplinary approach. The report applies this framework to ten countries and two sectors and uses the case studies as the primary data collection tool. These case studies provide detailed contextual analysis of the political, administrative and fiscal aspects of decentralization. The countries identified for the case studies are Angola, Ethiopia, Tanzania, Uganda, Kerala/India, Philippines, Guinea, Burkina Faso, Rwanda and Punjab/Pakistan. The sectors identified are health and education. The review of these case studies suggests that most of the local governments do not fare well on many assessment criteria of well-designed decentralization. In addition to the insubstantial discretion available to the local governments, accountability mechanisms are also not well developed.